The Impact of De-influencing on Social Media on Gen Z’s Purchase Intention: The Mediating Role of Source Credibility - Wiratha, Andre; Kemalasari, Nur (SAFE-Network, 2025)
De-influencing is a new trend that has attracted a lot of attention. Contrary to the usual product recommendations made by influencers, de-influencing involves influencers explicitly advising their audience not to buy certain products that they have reviewed in depth, or to be more discerning in their consumption of a product. This study examines the influence of de-influencing on Gen Z consumers' interest in purchasing technology products, with source credibility as the mediator. This quantitative study collected data from 385 Gen Z individuals who are active on social media, through Likert-scaled online questionnaires, utilizing simple random sampling. The data were then analyzed using SEM-PLS in SmartPLS 3. All hypotheses proposed were supported. The findings indicate that de-influencing on social media significantly affects the decline in Gen Z’s interest in purchasing technology products. The role of source credibility acts as a mediator in reinforcing de-influencing on the decline in purchasing interest. The role of source credibility effectively mediates how de-influencing affects the decline in interest in purchasing technology products. In addition, this study proposes alternative dimensions for measuring de-influencing, role of source credibility, and purchase interest. This study can provide insight to Gen Z so that they can be selective in purchasing technology products by finding out the advantages and disadvantages of the technology products they are going to buy, as well as comparing products with specifications that are not much different even though they are from different brands. This study focuses on the purchasing intentions of Gen Z consumers influenced by de-influencing and source credibility. Future research could benefit from incorporating other key factors, such as the intensity or content presented on social media, to provide a more comprehensive understanding.